O Papel de uma Team Manager no Futebol de Formação - Masculino vs. Feminino - Felicia Margarida Santos Silva (2024)
This internship report was carried out as part of the professional internship at the Sporting Clube de Braga, corresponding to the second year of the Master's Degree in Sports Management of the Faculty of Sport of the University of Porto. The report explores the role of Team Manager in youth sector of football in Portugal, highlighting the differences in the men's and women's departments. The study aims to understand the responsibilities, challenges and skills necessary for the effective performance of this crucial function in the development of athletes. It was also sought to evaluate the impact of Team Manager on the development of athletes and the general functioning of teams and the organization. The main objective of the report is to portray all the experiences lived throughout the internship at SC Braga, one of the biggest clubs in Portugal, which is present in various modalities and which acts on the largest national and international stages. The internship was divided by the men's training football department and the women's football department in the organization, having assumed and performed different functions and activities throughout this phase. The moments lived, the actions carried out, the functions assumed, the skills acquired and all the aspects essential to the good performance of a sports manager in an entity of such a size will be described. A critical reflection on the entire process will be carried out, and an analysis of the future perspectives, depending on all the skills acquired throughout the stage. In conclusion, I consider that the present stage has reached my expectations, having been a journey that contributed positively to my professional and personal development.